Comparison of Time and Cost Savings Using Different Cost Methodologies for Patient-Specific Instrumentation vs Standard Referencing in Total Ankle Arthroplasty. Issue 4 (7th November 2019) - Savage-Elliott, Ian; Wu, Victor J.; Wu, Isabella; Heffernan, John Timothy; Rodriguez, Ramon
Background: Patient-specific 3-D printing cutting blocks (PSI) have been used instead of traditional intramedullary cutting guides. We hypothesized that PSI would lead to significantly decreased operating room (OR) time and significant cost savings to our institution with noninferior radiographic outcomes and no difference in expected vs actual implant size when compared with standard referencing (SR). Methods: Patients who had undergone total ankle replacements at our institution from 2013 through 2016 were included in the study. Associations between demographic variables and postoperative alignment in the SR vs PSI group were calculated using the Wilcoxon rank-sum test and the intraclass correlation coefficient. The cost of the operation was calculated using both an institutionally based fixed cost of OR time and using Time Driven Activity Based Cost (TDABC) accounting. A total of 43 patients were included in the study, 13 in the SR group and 30 in the PSI group. Results: Operative time (168 vs 137 minutes) and tourniquet time (123 vs 113 minutes) were significantly lower in the PSI vs the SR group. PSI predictions were accurate 100% of the time for tibial components and 83% of the time for talar components. Average costs of TAA using PSI were significantly reduced by $7597.00 when using traditional OR accounting, whereas PSI was $836.00 more expensive on average using TDABC accounting. Conclusion: Further research is needed to determine the cost-effectiveness of PSI vs SR in TAA; however, it does appear to save time intraoperatively. The long-term effect on clinical outcomes requires further study. Level of Evidence: Level III, case-control study.